THE EFFECT OF LIQUID ORGANIC FERTILIZER CONCENTRATION ON GROWTH AND RESULS OF VARIOUS SWEET CORN LINES IN MARGINAL LAND USING A DRIP IRRIGATION SYSTEM - Bambang Supriyanta; Oktavia Sarhesti Padmini; Danar Wicaksono; Kundarto Kundarto (Jurnal Agrivet, 2020)
Utilization of the potential of marginal land with adequate water and nutrients is an important factor in increasing corn production. However, high porosity levels and low nutrient levels cause growth and production of corn is not optimal. The aim of this research is to obtain an irrigation technique combined with efficient fertilization in the sweet corn cultivation system in marginal land. The field research was carried out at Faculty of Agricultural Research Wedomartani, Depok Sleman Yogyakarta. The study was conducted from September 2019 to February 2020. The research aims to get best sweet corn line at various concentrations of liquid organic fertilizer in marginal land with a drip irrigation system.The research was arranged in a completely randomized design (CRD) with 3 replications. The first factor is sweet corn lines, which consists of 9 levels, namely, G1 (5042B), G2 (KD-11), G3 (KD-13), G4 (SB-11), G5 (SB-13), G6 (SB-14), G7 (SB-16), G8 (SB-21), and G9 (SB-22). While the second factor is the irrigation system combined with fertilization (fertigation) which consists of 3 levels, namely the drip irrigation system with a concentration of liquid supplement fertilizer 2 cc / L, 3 cc / L and 4 cc / L. The results showed that the drip fertigation system with a concentration of POC 3 cc / L was able to give a better effect on plant height and leaf length in sweet corn. SB / 1-3 lines was the best lines as prospective parents for making hybrid lines for plant height, leaf length, number of leaves and cob length.Keywords: lines, liquid organic fertilizer, sweet corn, marginal land, irrigation system